2023
DOI: 10.1177/07334648231159372
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Medium-Term Effects of Ageism on Loneliness Experienced During the COVID-19 Pandemic

Abstract: Loneliness, common in old age, may be partially attributed to ageism. The present study explored the short- and medium-term effect of ageism on loneliness experienced during the COVID-19 pandemic using prospective data derived from the Israeli sample of the Survey of Health, Aging and Retirement in Europe (SHARE) ( N = 553). Ageism was measured before the COVID-19 outbreak and loneliness in the summer of 2020 and 2021 using a direct single question. We also tested for age differences in this association. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…While the two-way interactions between SA and anxiety/avoidance were not significant, the three-way interaction of SA × anxiety × avoidance revealed that the negative effect of SA on loneliness was nullified for securely attached individuals. Previous literature has demonstrated the importance of both positive aging perceptions (e.g., Shiovitz-Ezra et al, 2023; Spitzer et al, 2022) and satisfaction with social networks (Kemperman et al, 2019) for reducing loneliness in late life. In this regard, Mikulincer and Shaver (2014) suggested that attachment anxiety may be more conducive to loneliness when compared to avoidance (see also Mikulincer & Shaver, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the two-way interactions between SA and anxiety/avoidance were not significant, the three-way interaction of SA × anxiety × avoidance revealed that the negative effect of SA on loneliness was nullified for securely attached individuals. Previous literature has demonstrated the importance of both positive aging perceptions (e.g., Shiovitz-Ezra et al, 2023; Spitzer et al, 2022) and satisfaction with social networks (Kemperman et al, 2019) for reducing loneliness in late life. In this regard, Mikulincer and Shaver (2014) suggested that attachment anxiety may be more conducive to loneliness when compared to avoidance (see also Mikulincer & Shaver, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First, as previously indicated, the cross-sectional nature of the study precludes us from establishing a causal relationship between SA, attachment, and loneliness. While longitudinal research has demonstrated a causal link between negative age perceptions and loneliness (Shiovitz-Ezra et al, 2023), other studies indicated the opposite direction (e.g., Santini et al, 2019), and further research is needed to clarify this issue. In this regard, the online nature of our study, together with the fact that it was based on a convenience sample of Israeli older adults may hinder the representativeness of our cohort (e.g., the distribution of gender), and it is important to examine the study model in additional older adult populations both within and outside Israel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ageism can have an impact on all age groups, there is research suggesting that the older adults are at greater risk of suffering from its prejudicial effects (Levy et al, 2022;Palmore, 2004). In fact, ageism was shown to raise detrimental consequences on older adults' health and wellbeing (Bergman et al, 2020;Chang et al, 2020;Gvili & Bodner, 2021;Kornadt et al, 2021;Levy et al, 2020;Schuurman et al, 2022;Shiovitz-Ezra et al, 2023;Wyman et al, 2018). A meta-analytic study reviewing data from 32 articles concluded that being stereotyped negatively im paired older people's cognitive and functional performance (Lamont et al, 2015).…”
mentioning
confidence: 99%